WILLINGNESS TO PAY FOR RECREATIONAL USES IN KAENNAKORN LAKE, KHON KAEN PROVINCE - Prasri, Sirorat; Udomwitid, Sommai (Journal of MCU Nakhondhat, 2020)
This research aims were to study the factors that affect the use of recreation services of Bueng Kaen Nakhon and to assess the willingness to pay for the use of Kaennakorn Lake, Khon Kaen province. The populations for this study were people in Khon Kaen municipality who used Kaennakorn Lake for recreation. The sample in this research, random accidental sampling methods were used. A total of 300 samples were used by questionnaires to analyze factors affecting the frequency of recreation services used in Kaennakorn Lake. Data analysis was performed using linear multiple regression. As for the assessment of willingness to pay for the use of Kaennakorn Lake public park use choice model analysis methods. The results of research found that the analysis of factors that affect the frequency of recreation services of Kaen Nakhon lake shows that there are 3 independent variables that are related to the number of times used in Kaennakorn Lake namely Age, To use the service for exercise and Travelling with the use of motocycles. A study of willingness to pay for recreational service of Kaennakorn Lake, Khon Kaen province consists of features music activities in the swamp track, green area. The results of analysis of indirect utility functions of Kaennakorn Lake for service users by using independent evaluators from various characteristics at least 95 percent confidence level found that the users of Kaennakorn Lake are willing to pay the most with the improvement of music characteristics in the garden. Which is equal to 2.77 Baht/time and the green area around the swamp 2.46 Baht/time.